Manajemen Laba: Kajian Berdasarkan Kinerja Keuangan, Tax Avoidance dan Kualitas Audit. - Yendrawati, Reni (Jurnal Akuntansi Manajerial, 2025)
This study aims to examine the effect of financial performance, tax avoidance, and audit quality on earnings management. The population of this study consists of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2018–2022. The sampling method used is purposive sampling, resulting in 320 samples that meet the specified criteria. Hypothesis testing is conducted using multiple linear regression analysis. The results indicate that financial performance, tax avoidance, and audit quality have a negative effect on earnings management. Practically, the findings of this study provide recommendations for investors to enhance their understanding of the underlying reasons behind manipulation typically carried out by managers, thereby helping investors mitigate the negative consequences of earnings management practices conducted by companies.